Leadership and effective institutional economics design in the context of education reforms - Wadim Strielkowski; Vyacheslav Volchik; Artyom Maskaev; Pavel Savko (Economies, 2020)
Nowadays, the most typical reforms in higher education are conducted through the reorganization of universities either in the form of a merger, acquisition, or new status attainment. As a result, universities which educate local leaders for their respective national economies and have a profound impact on the regional economic development, as well as the composition of the labor market and intellectual potential, often encounter negative economic outcomes. The reforms that are imposed by the policymakers "from above" often hamper the development of universities and prevent them from fulfilling their roles described above. The process of reforming higher education in Russia is in many ways similar to the changes in the higher education systems of other European countries, in particular in post-Communist transition economies. Firstly, this process went through the integration into the global market of educational services. Secondly, it proceeded with the rethinking of the role of the university as a self-sustainable business organization. Thirdly, it was concluded by an increase in the demand and accessibility of education using the advancements offered by the digital technologies. Our paper argues that focused and well-balanced economic institutional design might be required for the sustainable development of reorganized leading universities. The project perspective implies that it is necessary to develop an institutional design in relation to what the organization seeks to achieve (either as its regulator or reformer) and how it intends to achieve these goals. In connection with the foregoing, we propose the following principles of designing effective institutions for the sustainable development of reorganized universities: (i) preservation of education as a "mixed" good (i.e., one that has the features of both public and private goods); (ii) transparency of decision making; (iii) complementarity of institutional change; and last but not least (iv) reduction in transaction costs.
Keywords: B52; I21; O10; 330; complementarity; higher education; institutional changes; institutional economics; new public management; transaction costs; universities